Frequency characteristics of integral Hall sensor - D. Ha. Dao; V. R. Stempitsky (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The results of device-technological and schematic simulation of the silicon Hall sensor with the purpose of determine its dynamic characteristics are presented. The influence of the dimensions of the active region is investigated, the theoretical and actual values of the upper limit of the bandwidth of the Hall sensor are determined, taking into account the internal parasitic capacitance, and the presence and absence of a capacitive load. The characteristics of the Hall sensor combined on a single crystal with a differential amplifier are simulated.